Improvement of Diabetes Mellitus Symptoms by Intake of Ninjin'yoeito - Hosogi, Shigekuni; Ohsawa, Masahiro; Kato, Ikuo; Kuwahara, Atsukazu; Inui, Toshio; Inui, Akio; Marunaka, Yoshinori (Frontiers in Nutrition, 2018)
Diabetes mellitus is a well-known common disease and one of the most serious social problems in the worldwide. Although various types of drugs are developed, the number of patients suffering diabetes mellitus is still increasing. Ninjin’yoeito (NYT) is a formula used in traditional herbal medicines Japanese for improvement recovery from various types of medical disorders. However, the effect of NYT on diabetes mellitus has not yet been investigated. In the present study, we tried to clarify the action of NYT on the blood glucose level in diabetes mellitus model mice. We found that intake of NYT diminished the blood glucose level and insulin intolerance in skeletal muscle in streptozotocin (STZ)-induced diabetic mice. NYT treatment also improved acidification of interstitial fluid in the skeletal muscle in STZ-induced diabetic mice. The expression of sodium-coupled monocarboxylate transporter 1 (SMCT1) was increased in proximal, but not distal, colon of STZ-induced diabetic mice. The present study suggests that NYT is a useful formula to improve the hyperglycemia-induced various disturbance by increasing insulin-sensitivity via elevation of interstitial fluid pH.